Design of phase-coded transmitter and high sensitive receiver of radar system - Kien, Do Trung; Duong, Bach Gia; Thuong, Nguyen Quy; Hung, Nguyen Manh (VNU Journal of Science: Mathematics - Physics; Vol 25 No 2, 2009)
Abstract